The Expanding Role of Industrial Human Performance Technology in Corporate Sustainability. Issue 4 (2nd April 2013) - Watson, Brett
Abstract Many companies are embracing business goals that support corporate sustainability. As they do, technology, industrial processes, and regulatory requirements will become even more sophisticated. Current human performance technology research and application are heavily biased toward economic business outcomes such as sales, profit, and inventory. Human performance technology research and application must expand beyond purely business metrics and become intrusively involved in technical, industrial work processes. Industrial human performance technology specialists will be needed to analyze the human performance interface between people, technology, and equipment.